Steganography With End Of File - Sitohang, Zuvernius; Yohana Desma R. Munte; Pembinata Taringan; Hiskia Hasugian; Trihadi Pinem (Login : Jurnal Teknologi Komputer, 2024)
Steganography is the science and art of hiding secret messages in other messages, so that the existence of the message cannot be known by third parties. One method used in steganography is the EOF (End of File) message insertion method, which is inserting data at the end of a file by providing a special mark to identify the beginning and end of the data. This technique is used to insert data as needed, and the steganographed file does not appear to change visually or audibly, even though the file size becomes larger. In this regard, this technique can be applied to protect the copyright of digital products, such as software or multimedia, through digital watermarking techniques that use the EOF method to insert information or messages as permanent identification in digital files. In addition, in an effort to improve security, a technique for combining Blowfish cryptography with Hexa steganography is also proposed. This technique has advantages over DCS steganography, namely fewer pixel color changes, so that the inserted data is more difficult to detect and easier to maintain even if the stego image is processed or edited. The results of the study show that the combination of Blowfish cryptography with Hexa steganography is more effective than DCS steganography in protecting the inserted data. The test was carried out by analyzing the robustness of Hexa steganography using the PNSR test to determine the level of change in the original image and the inserted image.